Examining the Implementation of the "Right to Disconnect" in Practice - Bernik, Nejc; Šprajc, Polona; Jereb, Eva (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The research examined the implementation of the Right to Disconnect (RTD) in Slovenia, legislated in November 2024. The goal was to identify its advantages, opportunities, weaknesses, and impact on the work processes and employees in selected public and private sector organizations. Through structured interviews with HR managers, various implementation practices were identified, such as adjusting working time regulations, introducing automatic email responders, and separating work and personal communication tools. The results revealed that private sector organizations were generally better prepared for implementing RTD, whereas public sector organizations faced additional challenges, including administrative constraints and wage reform. The SWOT analysis highlighted the benefits of RTD, such as clearly defined working hours and increased employee awareness, while pointing out weaknesses like remote work, which, due to continuous accessibility, leads to employee overburdening. In conclusion, RTD represents an important step toward a more sustainable work environment. However, its successful implementation will require continuous adjustment of regulations, employee awareness-raising, and harmonization of practices within organizations.